2016
DOI: 10.1080/14789450.2016.1252675
|View full text |Cite
|
Sign up to set email alerts
|

Immunomic approaches for antigen discovery of human parasites

Abstract: Genetics combined with proteomics allows for a better understanding of parasite-host interactions and host immune responses. Immunomics elucidates that antigens are targets of induced or naturally acquired immunity (NAI), a promising solution to the challenge of eradicating human infections. High-throughput protein microarrays enhance rapid antigen discovery for the development of serodiagnostic tests/vaccines. Areas covered: This review systematically analyzes the emergence of protein microarrays as a powerfu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
26
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
2

Relationship

3
5

Authors

Journals

citations
Cited by 22 publications
(27 citation statements)
references
References 102 publications
1
26
0
Order By: Relevance
“…In summary, anti-rPoMSP4 sera cross-reacted against rPocAMA1 or rPowAMA1, and rPowMSP1 proteins; by contrast, they showed low reactivity with rPocMSP1 proteins. This result suggested that rPoMSP4 antigens were able to generate antibodies with broad immune responses against such important proteins (known to be associated with red blood cell invasion [15]), making them attractive candidates to induce a polyclonal immune response.…”
Section: Specificity Of Pomsp4-derived Antiseramentioning
confidence: 96%
See 2 more Smart Citations
“…In summary, anti-rPoMSP4 sera cross-reacted against rPocAMA1 or rPowAMA1, and rPowMSP1 proteins; by contrast, they showed low reactivity with rPocMSP1 proteins. This result suggested that rPoMSP4 antigens were able to generate antibodies with broad immune responses against such important proteins (known to be associated with red blood cell invasion [15]), making them attractive candidates to induce a polyclonal immune response.…”
Section: Specificity Of Pomsp4-derived Antiseramentioning
confidence: 96%
“…Hosts respond to malaria parasites by generating antibodies against parasite-derived antigens, and naturally acquired immunity is developed after repeated exposure to infections [13]. Notably, antibodies against merozoite antigens play a significant role in conferring immunity against malaria [14,15]. Asexual-stage antigens located on apical organelles or on the surfaces of merozoites offer considerable potential as components of vaccines against malaria.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Blood-stage vaccines point to target the subsequent disease-causing stage of the Plasmodium life cycle and may provide protection against disease severity, reducing blood stage asexual parasitaemia and transmission [17]. Merozoite surface protein 1 (MSP1) and apical membrane antigen (AMA1) are leading blood-stage malaria antigens and considered important vaccine candidates [15] , especially due to their association with protection in pre-clinical studies of mice and non-human primates [18][19][20] . Protection is associated with the induction of high-titre antibodies.…”
Section: Introductionmentioning
confidence: 99%
“…Hosts respond to malaria parasites by generating antibodies against parasite-derived antigens, and naturally acquired immunity is developed after repeated exposure to infections [14]. Notably, antibodies against merozoite antigens play a significant role in conferring immunity against malaria [15,16]. Asexual-stage antigens located on apical organelles or on the surfaces of merozoites offer considerable potential as components of vaccines against malaria.…”
Section: Introductionmentioning
confidence: 99%